Coastal flood risk reduction : the Netherlands and the U.S. Upper Texas coast - Brody, Samuel David; Lee, Yoonjeong; Kothuis, Baukje Bee (Elsevier, 2022)
This volume represents the culmination of a 5-year international research and education partnership funded by the US National Science Foundation (NSF) and more than 10 years of collaboration between Dutch and U.S. flood experts on the basic issue of how to protect society from growing flood risks. Multiple case studies integrating the fields of engineering, hydrology, landscape architecture, economics, and planning address the underlying characteristics of physical flood risks and their prediction; human communities and the associated built environment; physical, social, and built-environment variables; and mitigation techniques. In recognition of the lack of systematic research and the growing societal need to better understand flood impacts, this book provides an in-depth, comparative evaluation of flood problems and solutions in two key places: the Netherlands and the U.S. Upper Texas Coast. Both regions are extremely flood-prone and have experienced continual adverse impacts throughout their histories. For researchers in flood management, geographers, hydrologists, environmental studies, and social science as well as policymakers and decision-makers in flood management authorities and related industries, this book provides an essential resource.